Case Report: Prenatal diagnosis of fetal tetrasomy 9p initially identified by non-invasive prenatal testing - Jialing Yu; Na Chen; Min Chen; Min Shen; Yeqing Qian; Minyue Dong; Minyue Dong; Minyue Dong (Frontiers in Genetics, 2022)
Tetrasomy 9p is a rare syndrome characterized by fetal growth restriction, Dandy-Walker malformation, cardiac anomalies, and facial abnormalities and is discovered by ultrasound during the prenatal examination. Herein, we report a fetus of tetrasomy 9p without obvious phenotypic manifestations during the first trimester that was identified by non-invasive prenatal testing (NIPT). NIPT revealed that the gain of 9p24.3–9p11 that was approximately 46.36 Mb in size. Karyotyping of amniocytes indicated an additional marker in all metaphase. Chromosome microarray and fluorescence in situ hybridization on uncultured amniocytes revealed tetrasomic of 9p24.3q13, and that the supernumerary chromosome is a dicentric isochromosome consisted of two copies of the 9p arm. Taken together, it was indicated that the fetal karyotype was 47,XY,+idic (9) (q13), and that multiple techniques are crucial to the prenatal diagnosis.